Learning fencing - Barth, K.; Barth, B. (Meyer & Meyer Sport (UK) Ltd., 2017)
This book, written in a style easily comprehended by a child and containing motivating illustrations, was written with the youngest of athletes in mind. By inviting kids to complete individual tasks, to solve puzzles, to answer questions and to complete drawings, the book achieves the feel of an activity book. The little cartoon character "Foily" accompanies the reader throughout the book, as he offers tips and invites the child to practice independently. The contents correspond to the most basic level of fencing training. It is intended as a teaching tool for fencing instructors and trainers, to help promote understanding of the sport of fencing for fencing students, and to improve independence in training. For the parents of fencing children it is an important motivational companion to fencing instruction. Klappentxt